Biotechnology incubator an entrepreneurial hub for biotechnology innovation - Lacierda, Aldrich C.
The Biotechnology Incubator is a research and development laboratory and a technology business incubator geared towards innovation in research and development in the field of Biotechnology and also functions as an entrepreneurial hub for biotechnology and technology-based industries and products. The Research Laboratories aims to provide its users with the facilities to accommodate the infrastructure requirements for a number of research and development activities in the life sciences integrated with support and utility services. While the Business Incubator will serve as a platform for these research activities to become viable and innovative products and technologies. The architectural translation of these activities are open and closed laboratories accommodating the various research processes in the field, workspaces, office spaces and collaborative work and open areas for user interaction and very dynamic user profile and working environment. The model uses the system approach and the building science framework model. The design translation seeks to make the facility an avenue for the development of technology-based industries as well as create a pool of knowledge necessary for economic growth through user interaction-innovation through collaboration. The study aims to make the biotechnology industry an economic driver for the country through collaborative research and development activities through business incubation models that are suited to the Philippine setting and the science and technology infrastructure of the country.